PENGARUH PELATIHAN, MOTIVASI INTRINSIK DAN EKSTRINSIK TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) ULP BERASTAGI - Silalahi, Donalson; Saragih, Alvyoni (Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine and explain the influence of training, intrinsic and extrinsic motivation on employee performance. To achieve this goal, research was carried out at PT. PLN (Pesero) ULP Berastagi using the census as a sampling technique obtained a sample of 52 employees. The data used is primary and secondary data. By using multiple regression analysis as an analytical tool, the following results were obtained: Training has a positive and significant effect on employee performance, intrinsic motivation has a positive and significant effect on employee performance, extrinsic motivation has a positive and significant effect on employee performance. Variations in training, intrinsic and extrinsic motivation are able to explain variations in employee performance by 73.8 percent. Intrinsic motivation is the most important variable to maintain for employees with a bachelor's/diploma education and extrinsic motivation is a very important variable for employees with a high school education and the intrinsic motivation variable is a variable that has a consistent impact on employee performance.